DISTRIBUTION OF MOLUSC TYPES (Gastropoda and Bivalves) IN SEAMUS IN THE WATERS OF TANJUNG SALEH VILLAGE, MOROTAI ISLAND DISTRICT - Nurafni, Nurafni; Wahab, Iswandi; Padoma, Ummi Kulsum (Politeknik Kelautan dan Perikanan Dumai, 2024)
The vast seagrass field allows the number of biota that live associated with seagrass. One of the wealth of marine resources that is often found is mollusks such as snails, shellfish, octopus, cuttlefish and squid. Mollusks are found in coastal areas with seagrass beds as their habitat. One of the most commonly found mollusk groups in Bere Bere village waters is gastropod and bivalvia. Research Objectives To determine the distribution of mollusks in the waters of Bere-Bere Village. This study was conducted in October 2021 to January 2022 located in the waters of Bere-Bere Village, North Morotai District, Morotai Island Regency. Data collection uses the quadratic transect method to identify mollusks (gastropods and bivalvia) that are found in each square. The transect rope is pulled perpendicular to the sea along 50 m during the receding sea water starting from the zero point (0), to the point of 50 m, the square distance is 10 m while the transect distance is 25 m, while the distance between the station is 50 m, then the square is placed on Every distance of 10 m along the transect that can represent the locations that have gastropod and bivalvia samples. Organism found along the transect, in the squares observed and then identified using an identification book. Field work practices were found 11 types of gastropods (Conus Gladiator, Conus Littyus, Trochidae sp, Cerithiidae sp, Canarium sp, Muricodrupa fenestrata, Vexillum sp, Strombus Campbelli, Strombus Campbell , Conus Episcopatus, Conus Sulcatus, Conus Pennaceus) and 3 types of Bivalvia (Lambis Lambis, Pinna Muricata, Diloma Radula) which are spread on three stations in the waters of Bere-Bere Village.